White Unity and Prisoner-Officer Alliances. (August 2022) - Friedman, Brittany
The law enforcement badge is a prized possession for white supremacists. Broader patterns of alliances between law enforcement and civilian white supremacists are endemic to social order in the United States, both in free society and within prisons. Using archival methods on trusty systems in California prisons, I show the development of prisoner-officer alliances that reify the privileges of white power.